Administrative corruption and its effects on Russian entrepreneurs: a regional aspect. (4th March 2018) - Krylova, Yulia
Abstract : This study analyzes how administrative corruption on the part of regulatory agencies in Russia impacts entrepreneurial employment at the regional level. The combination of spatial regression analysis and expert interviews with entrepreneurs allows for the identification of a negative relationship between administrative corruption and the population of entrepreneurs in Russian regions. The study demonstrates that rent-seeking activities of regulatory agencies often lead to the problem of overregulation in the entrepreneurial sector, which manifests itself in additional bureaucratic procedures for doing business in Russian regions. The paper argues that Russian public authorities need to adopt regional policies aimed at improving the regulatory environment and decreasing excessive administrative procedures for entrepreneurs.